2012
DOI: 10.1371/journal.pone.0045301
|View full text |Cite
|
Sign up to set email alerts
|

Perspective Distortion from Interpersonal Distance Is an Implicit Visual Cue for Social Judgments of Faces

Abstract: The basis on which people make social judgments from the image of a face remains an important open problem in fields ranging from psychology to neuroscience and economics. Multiple cues from facial appearance influence the judgments that viewers make. Here we investigate the contribution of a novel cue: the change in appearance due to the perspective distortion that results from viewing distance. We found that photographs of faces taken from within personal space elicit lower investments in an economic trust g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 35 publications
4
51
0
Order By: Relevance
“…Recovering the distance of a face has a number of applications: as an additional cue to depth in scene analysis, as an indicator of the possible emotional valence of the picture [1], as a tool to study portraiture in classical paintings, and as a tool for forensic analysis of images [3]. Our experiments are encouraging, and are sufficient as a proof of principle to demonstrate feasibility.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Recovering the distance of a face has a number of applications: as an additional cue to depth in scene analysis, as an indicator of the possible emotional valence of the picture [1], as a tool to study portraiture in classical paintings, and as a tool for forensic analysis of images [3]. Our experiments are encouraging, and are sufficient as a proof of principle to demonstrate feasibility.…”
Section: Discussionmentioning
confidence: 70%
“…Psychologists [1] observed that portrait photographs taken from within personal space elicit lower investments in an economic trust game and lower ratings of social traits such as strength, attractiveness or trustworthiness. These findings could not be explained by width-to-height ratio, explicit knowledge of the camera distance or typicality of the presented faces, thus suggesting the existence of a facial cue influencing social judgments as a function of interpersonal distance.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar psychology based studied is presented in [5,6]. Here, Perona et al investigate the effects of perspective distortion as visual cue for social judgement of faces.…”
Section: Related Workmentioning
confidence: 99%
“…These differences are rather small, and they are typically not noticed explicitly by a casual observer viewing a single picture. However, these differences are available to the visual system and have a significant emotional impact; this was revealed by a number of psychophysical experiments that my collaborators and I carried out in the laboratory (Bryan et al, 2012;Perona, 2007). A closer (0.6-1.2 m) viewing distance makes the sitter seem more approachable, peaceful and friendly, while longer viewing distances (2.4 m and more) give the impression of aloofness and, relatively speaking, unfriendliness and hostility (see Fig.…”
Section: What Makes a Good Portrait?mentioning
confidence: 99%